Strong-Field phenomenology in alternative theories of gravitation - Franchini, Nicola (2020)
Assessing the validity of general relativity requires to test its principles and solutions in every possible regime. Up to date, general relativity is in agreement with weak-field tests of gravity and with binary pulsars observations, and it is consistent with the data coming from the detection of gravitational waves emitted by binaries of compact objects. Although general relativity fits the data well, a confrontation with alternative theories would make these results more robust. Such a direct comparison requires predictions for the systems in question in interesting theories beyond general relativity. The first step to compensate for this lack is to understand the physics of black holes and neutron stars within alternative theories of gravity.